Capsinoid Non Pungent Capcaisinoid Analog dan Potensinya dalam bidang Kesehatan dan Pangan - Dwinianti, Edia; Prasetyo, Frengky Hermawan Hadi (Program Studi Pendidikan Biologi, FKIP, Universitas Nusa Nipa, 2025)
Capsinoids are capsaicinoid analog compounds that have a low level of pungency. Although capsinoid has a low level of pungency, it has a role as a bioactive compound like capsaicinoid, but more comfortable to apply because it does not cause a burning sensation. The purpose of writing this article as a literature study on capsinoids related to biosynthesis, various mutations in the pAMT gene, the potential of capsinoids in the health and the food industry. This article was written based on a literature review of various international journal sources with 80% review sources published in the last 10 years which are then organized in a structured manner. The capsinoid biosynthesis process is similar to the capsaicinoid biosynthesis pathway which is formed through the combination of phenylpropanoid and fatty acid biosynthesis pathways. Mutations in the pAMT gene cause no addition of amide bonds to vanillin to form vanyllilamine, but form vanyllil alcohol which will condense with fatty acids to form capsinoids. Based on the results of several studies on chili pepper accessions with low pungency, pAMT gene mutation features are specific in the form of single nucleotide substitutions, short nucleotide insertions and insertions in the form of transposons and several pAMT mutant alleles have been detected. Capsinoids have antiobesity, antioxidant, antitumor and antidiabetic properties that have the potential to be utilized in the health sector. In addition, vanylil alcohol contained in capsinoids potentially be utilized in the food sector to provide aroma to food.